2005
DOI: 10.1002/ldr.680
|View full text |Cite
|
Sign up to set email alerts
|

Impact of grazing on soil biota in a Mediterranean grassland

Abstract: The effect of cattle grazing on the soil nematode and protozoan communities, and on microbial biomass, was measured in Israel's northern highlands. Three grazing areas were compared: (1) with 1Á1 cow ha À1 y À1; (2) 0Á55 cow ha À1 y À1; and (3) control-no grazing for almost 18 years.Soil samples were collected from the upper 10 cm level of each area (n ¼ 24), in autumn, before the onset of the rainy season, in order to analyse soil moisture, organic matter, total nitrogen, microbial biomass, soil respiration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…However, the abundance of soil amoeba increased significantly under moderate grazing (CG), but decreased in UG99, WG and HG compared to UG79. Li et al (2005) also found that the amoeba biodiversity was highest under moderate continuous grazing. Naked amoeba were the main species of amoeba in our study (data not shown).…”
Section: Soil Microbial Biomass and Activitymentioning
confidence: 90%
“…However, the abundance of soil amoeba increased significantly under moderate grazing (CG), but decreased in UG99, WG and HG compared to UG79. Li et al (2005) also found that the amoeba biodiversity was highest under moderate continuous grazing. Naked amoeba were the main species of amoeba in our study (data not shown).…”
Section: Soil Microbial Biomass and Activitymentioning
confidence: 90%
“…In these environments, soil loss and vegetation deterioration have increasingly been accelerated by improper use of land and water resources (Geist and Lambin, 2002;Ma et al, 2002;Lei et al, 2006;Wei et al, 2008;Zhao et al, 2013). The conversion of natural vegetation to cropland and overgrazing will therefore affect the storage of soil organic matter and soil nutrients (Li et al, 2005;Yu et al, 2012;Bruun et al, 2013). During the last few decades, land degradation associated with land use/cover changes in dryland ecosystems have been the focus of the study of land/vegetation processes and climatic change (Reid et al, 2000;Masoud and Koike, 2006;Reynolds et al, 2007;John et al, 2009;Bakr et al, 2010;Tsegaye et al, 2010;Schulz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Soil protozoa, and ciliates in particular, represent a very important microbial group within the soil community, with both a high abundance and a vital ecological role in respect to nutrient cycling, accelerating the turnover of soil bacterial biomass (Acosta-Mercado and Lynn, 2004), regulating the size and the composition of soil bacterial communities, stimulating ammonification and nitrification (Li et al, 2010a), and significantly enhancing the growth of plants and earthworms (Foissner et al, 2005). Moreover, ciliates play a major role within the soil microbial loop (Azam et al, 1983, Xu et al, 2014) since they regulate the growth of bacteria and other smaller protists, maintaining ecological stability (Clarholm, 1985, de Ruiter et al, 1993, Finlay and Esteban, 1998, Ekelund et al, 2002, Bonkowski, 2004, Li et al, 2005, Esteban et al, 2006, Puitika et al, 2007, Bielewicz et al, 2011, Geisen et al, 2015, Geisen et al, 2018), and can also be regarded as flagship taxa occupying a key position within soil food webs (Foissner et al, 2002, Foissner, 2005, Chao et al, 2006). Therefore, studies on their dynamics and their community structures should provide us with powerful means for assessing and monitoring changes in the biotic and/or abiotic soil conditions, and many ciliate taxa can be considered as markers of environmental stress in the soil ecosystem (Coppellotti and Matarazzo, 2000, Xu et al, 2011, Debastiani et al, 2016), as well as, for monitoring the major soil pollutants, contaminants and land use transformations (Lüftenegger et al, 1985, Foissner, 1987, Yeates et al, 1991, Foissner, 1999, Mayzlish and Steiberger, 2004).…”
Section: Introductionmentioning
confidence: 99%